Keywords linking method for selecting educational web resources a la ZigZag. (27th February 2007) - Andric, Mirjana; Devedzic, Vladan; Hall, Wendy; Carr, Leslie
The authors of the web-based courseware typically face problems such as how to locate, select and semantically relate suitable learning resources. This paper proposes a tool that supports the authors in their tasks of selection and grouping the learning material. The 'a la' (Associative Linking of Attributes) in Education, enhances the search engine results by extracting the attributes (keywords and document formats) from the text. The relationships between the attributes are established and visualised in a novel hypertext paradigm using the ZigZag principles. Browsing the related metadata provides a quick summary of the document and can hence help in faster determining its relevancy. Also, the proposed solution enables better understanding of why some resources are grouped together as well as providing suggestions for the further searches. The results of a user trial indicate high levels of user satisfaction and effectiveness.